2012
DOI: 10.4104/pcrj.2012.00068
|View full text |Cite
|
Sign up to set email alerts
|

Continuity, but at what cost? The impact of telemonitoring COPD on continuities of care: a qualitative study

Abstract: Managers and healthcare professionals face major challenges in meeting demands for both relationship continuity and continuity of clinical management in the development of telemonitoring services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 12 publications
(15 reference statements)
5
90
0
Order By: Relevance
“…34 Wootton 35 conducted a literature review on the use of telemedicine for the most common chronic diseases over the last 20 years and concluded that the evidence base for the value of telemedicine in managing chronic diseases is weak and contradictory. 19,36 Common among this and our previous studies are the patients' experiences of improved communication with, and trust toward, the professional caregivers and a sense of increased security. However, the success of telehealth depends on several factors, of which the type of technology is one.…”
Section: Discussionsupporting
confidence: 52%
“…34 Wootton 35 conducted a literature review on the use of telemedicine for the most common chronic diseases over the last 20 years and concluded that the evidence base for the value of telemedicine in managing chronic diseases is weak and contradictory. 19,36 Common among this and our previous studies are the patients' experiences of improved communication with, and trust toward, the professional caregivers and a sense of increased security. However, the success of telehealth depends on several factors, of which the type of technology is one.…”
Section: Discussionsupporting
confidence: 52%
“…; Mair, Hiscock, and Beaton ; Fairbrother et al. , ). After all, daily in‐home visits are not feasible, especially when patients live in remote or rural areas.…”
Section: Resultsmentioning
confidence: 99%
“…Knowing the patient allowed for contextualizing the tele‐homecare data relative to the individual patient's current health status, capability, and situation as well as for targeting nursing interventions to the patient's specific needs (Fairbrother et al. , ; Peeters et al. ; Sanders et al.…”
Section: Resultsmentioning
confidence: 99%
“…In our outpatient setting, COPD patients depending on disease severity are evaluated 1-4 times per year (meaning 0.5-2 h of consultations per year). According to our national reimbursement system, with our proposed system it would cost 80 Swiss francs per patient-year to detect one AECOPD early, so that the herein expended effort is not disproportionate, which has been a possible concern [10,12,17]. It is also conceivable to replace outpatient visits in stable patients by THC in the future to save resources.…”
Section: Discussionmentioning
confidence: 99%